A Method to Calculate the Dynamic Strain Tensor from Blast Vibration Records - Theory and Measurement Error Analysis - Ruilin Yang (International Society of Explosives Engineers, 2012)
"Blast vibrations are essentially a strain/stress wave propagating in rock or structures inthe vicinity of a blast. However, blast vibration has always been quantified in terms ofpeak particle velocity (PPV) or acceleration (PPA), and a meaningful relationshipbetween blast vibration and strain/stress has not been established. The determination ofthe dynamic strain from blast vibration may improve quantification of blast damage andselection of a blast vibration limit for critical structures or high walls. Dynamic strainrelates to rock mechanics or material strength more directly than peak particle velocity(PPV). This paper documents a method to calculate the three-dimensional dynamic straintensor from recorded blast vibration signals. The method is based on determination of thedisplacement gradient at a point of interest for each time instance during the vibrationduration. The method to calculate dynamic strain is applicable to generic seismicwaveforms including near and far field blast vibration from a production blast withmultiple blast holes. In order to minimize measurement errors the specifications of thespacing between monitors and the sampling frequency of the vibration recording aredescribed."